Dyslipidemia in the Russian Federation: population data, associations with risk factors - O. M. Drapkina; A. E. Imaeva; V. A. Kutsenko; A. V. Kapustina; Yu. A. Balanova; S. A. Maksimov; G. A. Muromtseva; M. B. Kotova; N. S. Karamnova; S. E. Evstifeeva; O. A. Litinskaya; M. S. Pokrovskaya; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study the prevalence of dyslipidemias and their association with various risk factors in the Russian population of men and women aged 35-74 years in 2020-2022.Material and methods. This work was carried out as part of the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation-3 (ESSE-RF3) study. The sample included 28731 men and women aged 35-74 years living in 15 Russian regions. Hypercholesterolemia (HC) was diagnosed with total cholesterol (TC) ≥5,0 mmol/l, while elevated low-density lipoprotein cholesterol (LDL-C) was considered ≥3,0 mmol/l, hypertriglyceridemia — with triglyceride levels ≥1,7 mmol/l, reduced high-density lipoprotein cholesterol (HDL-C) <1,0 mmol/l in men and <1,2 mmol/l in women. Associations were assessed using logistic regression after adjustment for socio-demographic characteristics, drinking status, presence of hypertension (HTN) and stroke.Results. The prevalence of hypertriglyceridemia in the Russian Federation in 2020-2022 was 58,8%, hypertriglyceridemia — 32,2%. The incidence of lipid-lowering therapy increased with age from 1% in the group of 35-44 years to 16% in the group of 65-74 years. On average, only 7,6% of study participants received lipid-lowering therapy. Significant associations of HC with HTN, obesity and alcohol abuse were identified. Similar results were obtained for elevated LDL-C levels, with the exception of alcohol abuse. In turn, a reduced HDL-C level was significantly associated with the lack of higher education, marriage, physical activity, smoking and the presence of diseases.Conclusion. The prevalence of lipid disorders in the Russian Federation in 2020-2022 remained at a high level. These disorders occurred more often in women, and they were better informed about their cholesterol levels and more often received lipid-lowering therapy. HTN, obesity, and some behavioral and social risk factors were associated with dyslipidemia.